Orally delivered siRNA targeting macrophage Map4k4 suppresses systemic inflammation - Aouadi, Myriam (2009)
Gene silencing by double-stranded RNA, denoted RNA interference, represents a new paradigm for rational drug design1. However, the transformative therapeutic potential of short interfering RNA (siRNA) has been stymied by a key obstacle—safe delivery to specified target cells in vivo2. Macrophages are particularly attractive targets for RNA interference therapy because they promote pathogenic inflammatory responses in diseases such as rheumatoid arthritis, atherosclerosis, inflammatory bowel disease and diabetes3. Here we report the engineering of β1,3-d-glucan-encapsulated siRNA particles (GeRPs) as efficient oral delivery vehicles that potently silence genes in mouse macrophages in vitro and in vivo. Oral gavage of mice with GeRPs containing as little as 20 µg kg(−1) siRNA directed against tumour necrosis factor α (Tnf-α)depleted its messenger RNA in macrophages recovered from the peritoneum, spleen, liver and lung, and lowered serum Tnf-α levels. Screening with GeRPs for inflammation genes revealed that the mitogen-activated protein kinase kinase kinase kinase 4 (Map4k4) is a previously unknown mediator of cytokine expression. Importantly, silencing Map4k4 in macrophages in vivo protected mice from lipopolysaccharide-induced lethality by inhibiting Tnf-α and interleukin-1β production. This technology defines a new strategy for oral delivery of siRNA to attenuate inflammatory responses in human disease.